Effects of SRP Vaccine in Reducing E. coli O157:H7 in Cattle - A. B. Thornton; D. U. Thomson; J. T. Fox; G. H. Loneragan; D. Burkhardt; T. G. Nagaraja (Kansas Agricultural Experiment Station Research Reports, 2007)
Cattle are the main reservoir ofEscherichia coliO157:H7, which is a foodborne pathogen that causes bloody diarrhea in adults and kidney damage in children .E. coliO157 is shed in the feces of cattle, which can be a contamination source of water, ground beef, fresh vegetables, and unpasterized milk and fruit juices. In 2003, shiga-toxin producingE. coliO157:H7 caused 73,000 illnesses, which resulted in over 2,000 hospitalizations and 60 deaths in the United States. The estimated annual cost of this illness was $405 million, which included $370 million for premature deaths, $30 million for medical care, and $5 million for lost productivity. Strategies to reduce this food borne illness must be further investigated. A new vaccine technology targetingE. coliO157:H7 in hopes of reducing the colonization of this pathogen in beef cattle has been developed (Epitopix, LLC, Wilmar, MN). This vaccine was designed to block the transport of iron into the bacterial cell, which is an essential nutrient needed for the survival of this microorganism. Previous trials showed that this vaccine elicited an immune response and reduced fecal shedding of the pathogen in five-month old Holstein steers. The purpose of this experiment was to further evaluate the efficacy of this new siderophore receptor/porin protein (SRP) technology by analyzing fecal shedding and immune responses of mixed-breed calves orally inoculated withE. coliO157:H7.
Keywords: beef cattle